Effect of the environment and fasting on the lipid and fatty acid composition of Diplodom patagonicus - Pollero, Ricardo José (1981)
Some effects of food, habitat and temperature on the lipid composition of a freshwater mollusk, Diplodom patagonicus, were studied. Animals kept and fasted up to 60 days in an aquarium at 9 C and 20 C showed a decrease of the total lipid content that corresponded to a decrease of triacylglycerols and diacylglycerol ethers. This decrease evoked an increase of polar-to-nonpolar lipid ratio. However, no significant change in the total fatty acid composition was shown. Moreover, a decrease of temperature from 20 C to 9 C decreased the incorporation of labeled linoleic and α-linolenic acid into the lipids, but did not modify the unsaturated: saturated acid ratio of the mollusk lipids during this period. A change of habitat from lake to estuary changed very significantly the fatty acid composition of the animal. The ω6 acids, linoleic and arachidonic, typical of D. patagonicus living in the lake, were partially replaced by ω3 acids. That this change was due to a change of food composition was indicated by the fatty acids of corresponding sediments. Therefore, the fatty acid composition of D. patagonicus is highly sensitive to food composition and varies little with temperature and seasonal changes.